LEADERSHIP STYLE, ORGANIZATIONAL COMMUNICATION, AND EMPLOYEE PARTICIPATION TO INCREASE EMPLOYEE READINESS IN FACING CHANGES IN BUSINESS ENVIRONMENT - Puspasari, Novia; Sukmawati, Anggraini; Sumertajaya, I Made (Jurnal Aplikasi Manajemen, 2017)
The aim of this study is to analyze the influence of leadership style, organizational communication, and employee participation on employee readiness for changes in business environment at Small-Medium Enterprises (SMEs) in creative economy industrial sector, in partnership program of PT Pertamina (Persero) with criteria of having been established for at least 5 years, employing 20-99 personnels. Based on the criteria, only 3 SMEs meet the requirements; they are located in Bogor, Depok and Jakarta. This study involved 40 people, consisting of SME owners and employees. This study conducted descriptive analysis as well as Structural Equation Modeling PLS. The study resulted that both leadership style and organizational communication brought positive impact directly to employee participation, as well as positive impact indirectly to employee readiness for changes in business environment. In addition, employee participation also created direct positive influence to employee readiness for changes in business environment. The study results also suggest owners to actively communicate regarding planning for changes to improve employee participation. Nonetheless, both SME owners and PT Pertamina (Persero) shall continuously conduct relevant trainings.